Efektivitas Neurofeedback Training Terhadap Kognitif dan Perilaku Pada Anak Autis Di Pusat Kajian Psikologi Magister Psikologi Pascasarjana Universitas Medan Area - Nur Husna Azizah Harahap; Sri Milfyetty; Risydah Fadilah (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2021)
This study aims to test the effectiveness of Neurofeedback Training in overcoming cognitive and behavioral problems in children with autism. The hypothesis that is done is Neurofeedback Training which is effective in overcoming cognitive and behavioral in children with autism. This study used a Quasi Experiment One Group Pretest-Posstest Design. The sampling technique was using purposive sampling and the sample in the study was 1 person. The research instrument is a measurement of brain wave activity called Electroencephalography. Data analysis in this study resulted in two types of data, namely quantitative and qualitative. The resulting quantitative data are the results of the scores and graphs of measuring the brain waves of children with autism through Neurofeedback and qualitatively obtained from the results of the assessment using DSM V, the results of parent interview reports, and the results of observations. The hypothesis proposed is that Neurofeedback Training is effective in overcoming cognitive and behavioral problems in children with autism. The conclusions in this study are: 1. Neurofeedback training is effective in overcoming cognitive problems in children with autism, this is indicated by an increase in the Beta value of 13 Hz. 2. Neurofeedback Training is effective in overcoming behavioral problems in children with autism, this is shown by increasing the Sensorymotor Rhytm (SMR) value of 5 Hz. 3. Neurofeedback Training is effective in overcoming cognitive and behavioral problems in children with autism, this is shown by increasing the Alpha value of 18 Hz, the Sensorymotor Rhytm value of 5 Hz and the Beta value of 13 Hz. Based on the conclusion, the proposed hypothesis is accepted. For future researchers who want to research Neurofeedback, they can use a wider range of research subjects in children with special needs with different disorders.